Rural Infrastructure ant Its Impact on Agricultural Growth in India: An Empirical Analysis - Kaur, Kirandeep; Kaur, Mandeep (European Scientific Journal, ESJ, 2023)
The present paper attempts to find the impact of the rural infrastructural facilities on agricultural growth in India. It analyzes the trends in rural infrastructure variables and value of output from agriculture sector over the study period 1990-19 to 2017-18. Compound annual growth rates (CAGR) have been worked out to find the changes in area, production and yield of agriculture output. To investigate the relationship between infrastructure variables and value of agricultural output the regression analysis has been used. In present study the rural infrastructure includes irrigation facilities, fertilizer consumption, primary agricultural credit societies, electric supply, agricultural markets, and road network in rural areas. Study finds that there is significant impact of irrigation, fertilizer consumption, credit, regulated agricultural markets and road infrastructure on agricultural output. The impact of electric pump, tractors and village electrification has not found statistically significant. It implies that infrastructure facility like roads, irrigation and electricity have a more direct effect on agriculture growth than personal infrastructure like electrical pumps and tractors. This finding validates the conclusion regarding positive and significant relationship between rural infrastructure and agriculture growth in India.